Design of an Expert System for Diagnosing Cat Diseases Caused by Fungi or Viruses Using the Certainty Factor Method - Kusuma, Retno Ayu; Novriyenni, Novriyenni; Syahputra , Siswan (Journal of Mathematics and Technology (MATECH), 2024)
The health and beautiful appearance of pets is important because treating these diseases requires more money. If the pet is infected with a disease that can be transmitted, then as the owner you have to do something to find out the type of disease and treatment, one of which is cats. However, many keepers still do not know the symptoms of diseases suffered by cats. So the treatment that should have been carried out at the beginning is delayed and the cat is no longer healthy because it is already suffering from an illness. The lack of veterinarians is also one of the factors causing delays in treatment for cats. For this reason, we need a system that can store knowledge about the symptoms and treatment process of the disease experienced by the cat. Expert system is a system that adopts human knowledge into a computer so that the computer is able to solve problems the way an expert works. Meanwhile, the Certainty Factor Method is a method that defines a measure of certainty regarding facts or rules to describe an expert's confidence in the problem being faced. Based on the results of the trials carried out, it was found that the highest confidence value was in the symptoms of Ringworm disease with a confidence value of 91%.